Why am I not in my neighborhood? Social sustainability as a challenge of the residential care system for minors - Sarasa Camacho, Hodei (Cuadernos de Trabajo Social, 2025)
Reducing the current high number of minors in residential care is one of the current challenges facing the child and adolescent protection system in Spain. However, the current reality shows that this deinstitutionalization is not taking place to the extent intended; in many cases, residential foster care resources are "overflowing", mainly with adolescent minors.In parallel to these efforts to reduce the number of institutionalized adolescents, it would seem to be a public responsibility to safeguard the best psychosocial development during, at least, the time they remain under the care of the public administration.To this end, during this institutionalization process, the entities responsible for the protection of these adolescents make a strong effort to improve the relationship between them and their families of origin. But what happens with the relationship and protective potential of other agents during the residential foster care process?This article focuses on two protective agents that have been little mentioned so far and that could be key to this better development: the territorial communities of origin and the original peer groups that interact in these communities.First, the paper analyzes to what extent the protective potential of these agents is contemplated; second and based on this analysis of the discourses of the minors under guardianship, the article presents a series of recommendations, as effective strategies for practice.
Keywords: child welfare; residential child care; adolescence; community action; social capital